Resistant Transparency and Nonprofit Labor: Challenging Precarity in the Art + Museum Wage Transparency Campaign. (August 2021) - Südkamp, Carolin M.; Dempsey, Sarah E.
Drawing upon contemporary academic debates about nonprofit worker precarity combined with needed theoretical re-orientations toward transparency, this paper explicates the situated communication practices and politics of resistant transparency. Resistant transparency describes communication aimed at revealing and publicizing previously obscured or hidden wage data and employment conditions to challenge powerful actors. Resistant transparency involves dynamic shifts in control over information, modes of in/visibility, and surveillance of powerful actors. We develop the case of Art + Museum Transparency, a collective of arts and museum workers employing Google spreadsheets and Twitter to publicize salary information and challenge norms of self-sacrifice and unpaid labor. Moving beyond an understanding of transparency as an institutional demand, our analysis develops how technical affordances shaped the collective's efforts. We argue that transparency functions as a resistant communicative practice with potential for increasing worker voice and furthering the goals of collective resistance to precarious work across sites of employment.